2015
DOI: 10.1063/1.4915311
|View full text |Cite
|
Sign up to set email alerts
|

Superior optical nonlinearity of an exceptional fluorescent stilbene dye

Abstract: Strong multiphoton absorption and harmonic generation in organic fluorescent chromophores are, respectively, significant in many fields of research. However, most of fluorescent chromophores fall short of the full potential due to the absence of the combination of such different nonlinear upconversion behaviors. Here, we demonstrate that an exceptional fluorescent stilbene dye could exhibit efficient two- and three-photon absorption under the excitation of femtosecond pulses in solution phase. Benefiting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The observation of harmonic generation can be regarded as a supporting evidence for MPA upconversion lasing. In fact, the harmonic generation from materials was ignored for a long time, and only a small amount of reports about the observation of coexistence between MPA fluorescence and two‐harmonic generation can be found up to date . In comparison to the organic medium solution and other disordered nanoparticle systems, the microwire/nanowire with non‐centrosymmetry structure will possess an excellent MPA ability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation of harmonic generation can be regarded as a supporting evidence for MPA upconversion lasing. In fact, the harmonic generation from materials was ignored for a long time, and only a small amount of reports about the observation of coexistence between MPA fluorescence and two‐harmonic generation can be found up to date . In comparison to the organic medium solution and other disordered nanoparticle systems, the microwire/nanowire with non‐centrosymmetry structure will possess an excellent MPA ability.…”
Section: Resultsmentioning
confidence: 99%
“…Growth and Characterization of the MWs : The gain media ZnO MWs were grown using the VLS growth method . The growth method has been illustrated in detail elsewhere . The morphology of bare MW was characterized by field emission scanning electron microscopy (FESEM, Hitachi S4800).…”
Section: Methodsmentioning
confidence: 99%
“…There have been many reports of 3PA processes resulting from 2PA followed by excited‐state absorption (ESA), but far fewer describing instantaneous 3PA employing low repetition‐rate femtosecond pulses . Of these, very few have undertaken nonlinear‐absorption spectral‐dependence studies, although such studies are needed to identify the specific wavelengths in the telecommunications band at which the instantaneous 3PA coefficient is maximized ,,,,. From the limited studies thus far, fluorene‐based monomers and oligomers have been shown to be particularly efficient three‐photon absorbers,,, exhibiting three‐photon‐excited fluorescence (3PEF)‐derived 3PA cross‐sections as high as 4.6×10 −76 cm 6 s 2 at 1330 nm .…”
Section: Figurementioning
confidence: 99%
“…The MPA process refers to the material simultaneously absorbing multiple long-wavelength excited photons to generate one short-wavelength emitted photon 3 . This process usually occurs in several kind of materials such as dye molecules, AIE nanoparticles, quantum dots, etc [4][5][6] . The occurrence of MPA emission requires extremely high excitation light energy, so the femtosecond pulse laser is usually used as the excitation light source, which is quite expensive.…”
Section: Introductionmentioning
confidence: 99%